Biofortified High Zinc Wheat: The Traditional Staple Dietary Food to Address Malnutrition in Pakistan - Baloch, Qadir Bux; Mujahid, Muhammad Yaqub; Noreen, Sibgha; Makhdum, Muhammad Iqbal (International Journal of Endorsing Health Science Research, 2018)
Background: The footprints of zinc dietary nutrient deficiency are resulting in a widespread burden of stunting, wasting and underweight in children under five years, and reproductive development in women over a population of 100 million in Pakistan. The zinc malnutrition could be addressed by consumption of biofortified high zinc wheat flour, a staple food, in complemented with food supplementation, food diversification and food fortification interventions in the country. Methodology: This evidence-based research publication focused on micronutrients malnutrition on human health and capital. Literature was taken from last 20 years papers published in several peers reviewed scientific journals. Papers regarding malnutrition were mainly focused. The primary data was collected from R&D institutions and secondary data from Pakistan National Nutrition Survey 2011. Various sites, viz. www.harvestplus.org, www.ifpri.org, http://www.ars.usda.gov/ba/bhnrc/ndl, http://data.unicef.org: www.fao.org: http://wholibdoc.who.int/publications were also visited. Results: In Pakistan, the recently released biofortified high zinc wheat variety “Zincol-2016” had a higher quantum of 37 mg Zn kg-1 compared to 25.0 mg Zn kg-1 in grain portion in other commercially grown wheat varieties. Upon consuming biofortified wheat flour, zinc concentration increased from 681.3 to 792.3 µg L-1 in human plasma. Furthermore, even an increase in dietary zinc by an amount of 2.0 mg Zn capita-1 day-1 may result in halving the endemic problem of zinc malnutrition, with a little change in food diversity pattern. Conclusion: The consumption of biofortified high zinc wheat variety “Zincol-2016” containing 37 mg Zn kg-1 compared to 25.0 mg Zn kg-1 in conventional wheat varieties could result in alleviating zinc malnutrition to the extent of 50% in the malnourished population. Thereby, it is a potential complementary staple food with other contemporary interventions to address malnutrition in Pakistan.